EARTH'S MAGNETIC FIELD: OCEAN CURRENT CONTRIBUTIONS TO VERTICAL PROFILES IN DEEP OCEANS - Lilley F.E.M.; White A.; Heinson G.S. (My University, 2001)
The Earth's main magnetic field, arising in the core, should, in the ocean, have a well-defined uniform gradient with depth. Superimposed upon this uniform gradient may be magnetic signals due to a variety of sources. These include crustal magnetization, the transient fluctuations arising external to the Earth and causing secondary induced fields within it; and, the focus of the present paper, magnetic signals arising from the motional induction of seawater moving in the steady main magnetic field of Earth. There are circumstances where theory predicts such motionally-induced magnetic fields to be of order 102 nT, and to vary with depth in a way which is directly related to the velocity profile. Exploratory soundings of the magnetic field with depth have been made in the oceans around Australia, both to test these predictions, and to investigate the practicability of measuring such profiles. The magnetic field parameter observed has been that of the ‘total field’, which should sense the component of the ocean velocity which lies in the magnetic meridian. The magnetometer has been lowered by cable from a ship and also operated free-fall to the seafloor (and return). The observations appear both to confirm the theoretical gradient of the main field where there is no ocean current and, where ocean currents exist, to give evidence of their profiles resolved in the direction of magnetic north. In particular, observations taken in an eddy of the East Australian Current show the correct contrast in sign for north and south flowing streams.